Spatial pattern analysis in plant ecology - Dale, Mark R. T. (Mark Randall Thomas), 1951- (Cambridge studies in ecology., 1999)
The predictability of the physical arrangement of plants is a crucial aspect of vegetation. This book describes and evaluates methods for analysing a variety of characteristics of spatial pattern. Worked examples and examples from real field studies, together with numerous line figures, help guide the reader through the text.